Desarrollo de un sistema de liberación basado en nanopartículas de quitosano para la optimización del uso terapeútico de interferón alfa - Cánepa, Camila Belén (2018)
Interferon alpha (IFN?) is protein approved for the treatment of viral and oncological\npathologies, which must be administered parenterally. Our aim was to develop a delivery\nsystem for IFN?-2b by means of a simple, reproducible and economical methodology that\nwould enable its oral administration. Spherical chitosan nanoparticles (CTNPs) of 47 nm were\nobtained by ionotropic gelation. These were stable at pH 5.0-7.0 and mucoadhesive. In\naddition, CTNPs were safe and showed a moderate permeability through colonic cells in vitro.\nThe encapsulation efficiency of the drug loaded system (CT-IFNNPs) was 98%; the\nphysicochemical characteristics were not altered with respect to the unloaded CTNPs. In vitro\nantiviral activity of the CT-IFNNPs was analogous to that of the commercial IFN?. After oral\nadministration of CT-IFNNPs (0,3MIU) to Balb/C mice, IFN? was detected in plasma.\nFurthermore, 3 daily doses of CT-IFNNPs induced the production of pro-inflammatory\ncytokines in spleen, to a greater extent than the pristine IFN? administered subcutaneously,\nsuggesting biological functionality of the drug. Thus, we report for the first time the\ndevelopment of a formulation that enabled the absorption of orally administered IFN?,\nelucidating a new avenue for non-invasive and eventually safer administration routes for\nhighly labile biological drugs, compared to conventional parenteral therapy.